2015
DOI: 10.1089/fpd.2014.1792
|View full text |Cite
|
Sign up to set email alerts
|

Association of CRISPR/Cas Evolution withVibrio parahaemolyticusVirulence Factors and Genotypes

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR), which is considered to be an immune system for bacteria, has been widely used as a tool for genome editing and genotyping. It has also been reported to be associated with virulence factors in some bacteria. To understand the role of CRISPR in the virulence and evolution of pathogenic Vibrio parahaemolyticus, 154 V. parahaemolyticus strains isolated from clinical samples and 54 strains from food samples taken in Shenzhen, China were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
4
24
1
1
Order By: Relevance
“…Various patterns of spacers in the CRISPR-Cas system have been reported for subtyping C. jejuni , Mycobacterium tuberculosis , Erwinia amylovora , V. parahaemolyticus and S. enterica [ 8 , 20 , 41 ]. Analysis of orphan CRISPR spacers derived from 14 clinical Enterococcus faecalis isolates indicates two groups of clonal strains which correlates to the Multilocus sequence typing (MLST) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various patterns of spacers in the CRISPR-Cas system have been reported for subtyping C. jejuni , Mycobacterium tuberculosis , Erwinia amylovora , V. parahaemolyticus and S. enterica [ 8 , 20 , 41 ]. Analysis of orphan CRISPR spacers derived from 14 clinical Enterococcus faecalis isolates indicates two groups of clonal strains which correlates to the Multilocus sequence typing (MLST) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alternative methodologies for genotyping and correct identification should be used in addition to traditional tools. CRISPR-Cas systems have been used for identifying: (i) industrial microbes, including: Streptococcus thermophilus, Lactobacillus casei , and Lactobacillus paracasei (Horvath et al, 2008 ; Broadbent et al, 2012 ; Smokvina et al, 2013 ), (ii) food pathogens: Lactobacillus buchneri (Briner and Barrangou, 2014 ) and (iii) human pathogens: Campilobacter jejuni (Kovanen et al, 2014 ), Clostridium difficile (Andersen et al, 2016 ), Mycobacterium tuberculosis (Sola et al, 2015 ; Freidlin et al, 2017 ), Salmonella enterica (Shariat et al, 2013 , 2015 ; Bachmann et al, 2014 ; Almeida et al, 2017 ; Xie et al, 2017 ), Vibrio parahaemolyticus (Sun H. et al, 2015 ), Yersinia pestis (Barros et al, 2014 ; Xu et al, 2017 ) and Yersinia pseudotuberculosis (Koskela et al, 2015 ), among others. However, genotyping through CRISPR technologies has been seldom applied to probiotics, with few exceptions in Lactobacillus rhamnosus (Douillard et al, 2013 ) and Lactobacillus gasseri (Sanozky-Dawes et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ]. Furthermore, clinical isolates of Pseudomonas aeruginosa lack CRISPR resistance despite crRNA expression, and several virulent clinical isolates of pathogenic Vibrio parahaemolyticus [ 46 ], Shigella [ 47 ], pathogenic Clostridium jejuni [ 48 ] and Mycoplasma gallisepticum [ 49 ] seem to lack CRISPR resistance. While these studies have suggested a causal role played by CRISPR inactivity in the gain of virulence of clinical isolates, we propose an alternative mechanism: reduced growth rate in virulent strains induces selection for reduced CRISPR activity.…”
Section: Discussionmentioning
confidence: 99%